Synthesis, crystal structure, spectroscopic and electrochemical characterization of the dinuclear complex {tetra-mu-[(+/-)-2-(p-methoxyphenoxy)-propionato-O,O']bis(aqua)dicopper(II)} - Cavicchioli, Mauricio; Massabni, Antonio Carlos [UNESP]; Guilherme, Luciana Rebelo; Castellano, Eduardo Ernesto; Paduan-Filho, Armando; da Costa Ferreira, Ana Maria (Springer, 2007)
Structural, electrochemical and spectroscopic data of a new dinuclear copper(II) complex with (+/-)-2-(p- methoxyphenoxy) propionic acid are reported. The complex {tetra-mu-[(+/-)-2-(p-methoxyphenoxy)propionato-O,O']-bis( aqua) dicopper(II)} crystallizes in the monoclinic system, space group P2(1)/n with a = 14.149(1) angstrom, b = 7.495(1) angstrom, c = 19.827(1) angstrom, beta = 90.62(1) and Z = 4. X-ray diffraction data show that the two copper(II) ions are held together through four carboxylate bridges, coordinated as equatorial ligands in square pyramidal geometry. The coordination sphere around each copper ion is completed by two water molecules as axial ligands. Thermogravimetric data are consistent with such results. The ligand has an L' type shape due to the angle formed by the beta-carbon of the propionic chain and the linked p-methoxyphenoxy group. This conformation contributes to the occurrence of a peculiar structure of the complex. The complex retains its dinuclear nature when dissolved in acetonitrile, but it decomposes into the corresponding mononuclear species if dissolved in ethanol, according to the EPR measurements. Further, cyclic voltammograms of the complex in acetonitrile show that the dinuclear species maintains the same structure, in agreement with the EPR data in this solvent. The voltammogram shows two irreversible reduction waves at E-pc = -0.73 and -1.04 V vs. Ag/AgCl assigned to the Cu(II)/ Cu(I) and Cu(I)/Cu degrees redox couples, respectively, and two successive oxidation waves at E-pa = -0.01 and +1.41 V vs. Ag/AgCl, assigned to the Cu degrees/Cu(I) and Cu( I)/Cu( II) redox couples, respectively, in addition to the oxidation waves of the carboxylate ligand.